Factors associated with the increased risk of dementia found in the Torres Strait. (5th August 2021) - Russell, Sarah G.; Quigley, Rachel; Thompson, Fintan; Sagigi, Betty; Miller, Gavin; LoGiudice, Dina; Smith, Kate; Pachana, Nancy A.; Strivens, Edward
Abstract: Objective: To identify the specific risk factors for dementia in the Torres Strait. Methods: This research was conducted as part of a cross‐sectional dementia prevalence study conducted in the Torres Strait. Participants underwent a comprehensive health assessment, where data on risk factors were collected, and a Geriatrician assessment, which was used to establish dementia diagnoses. Results: A total of 276 Torres Strait residents aged between 45 and 93 participated in the study. Cerebrovascular disease, chronic kidney disease and older age were the most significant risk factors in this population. Once adjusted for age, cerebrovascular disease, chronic kidney disease, diabetes, low education and problems with mobility and incontinence were significantly associated with dementia. Conclusions: Reducing dementia risk in the Torres Strait requires multifactorial interventions to address potentially modifiable risk factors with a particular focus on addressing the development of chronic midlife diseases.